PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PABRIK UNIT USAHA KAYU ARO PT. PERKEBUNAN NUSANTARA VI (PERSERO) WILAYAH JAMBI - M Zahari; Ubaidillah Ubaidillah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2014)
Management is a process that consists of the functions of planning, organizing, leadership and control of the activities of human resources and other resources to achieve the stated goals efficiently. From the results of hypothesis testing can be concluded that the work environment variables (X) is able to explain the variable (Y) or employee productivity is 2.3% and 97.7% of the studied variables outside. From the opinion of management experts who deal can be concluded that the management process is the planning, organizing, leadership and control of the activities of human resources to achieve the goals it has set. In this study, there are indicators of several variables, namely work environment variables. Employee relations, environmental noise level work, work regulations, lighting, air circulation, security. While productivity indicators covering ability, increasing the results achieved, morale, self-development, quality, efficiency. Based on simple linear regression equation calculates, obtained the following mathematical equation Y = 41.935 + 0.173 X from the following equation looks positive impact on the environment kerjater facing employee productivity Business Unit Kayu Aro. PT. Perkebunan Nusantara VI (Persero) Region Jambi. If the work environment experienced a 100% increase in the productivity of employees in the Business Unit Kayu Aro PT. Perkebunan Nusantara VI (Persero) Region Jambi evident from the regression coefficient sebesar17,3% This fact shows that the working environment had no effect on employee productivity Business Unit Kayu Aro. PT. Perkebunan Nusantara VI (Persero) Region Jambi. Work environment Business Unit  Kayu Aro. PT. Perkebunan Nusantara VI (Persero) Region Jambi being with an average score of 298, while productivity was with an average score of 297, which means that the working environment and productivity hypothesis Business Unit Kayu Aro PT. Perkebunan Nusantara VI (Persero) Region Jambi rejected.